Yellow fever vaccine usage in the United States and risk of neurotropic and viscerotropic disease: A retrospective cohort study using three healthcare databases. Issue 5 (31st January 2022) - Ledlie, Shaleesa; Ricci, Christina; Pan, Chunshen; Rojas, Andrey; Khromava, Alena; Li, Lin
Highlights: We assessed greater than 10 years of civilian YF vaccinee data in 3 US healthcare databases. Most YF vaccinees were aged < 60 years (largest age group 18–29 years). Few vaccinees (<1%) had medical conditions predisposing them to immunosuppression. Incidence proportion of neurotropic disease ranged from 0 to 3.04 per 100, 000 vaccinees. There were no viscerotropic cases identified across the three databases assessed. Abstract: Background: Yellow fever (YF) vaccines are highly effective and have a well-established safety profile despite the risk of rare serious adverse events (SAEs), vaccine-associated neurotropic (YEL-AND) and viscerotropic disease (YEL-AVD). This study aimed to describe US civilian YF vaccine usage, the population characteristics and pre-existing immunosuppressive medical conditions among those vaccinated, and to provide updated risk estimates of neurotropic and viscerotropic disease post-vaccination. Methods: A retrospective cohort study was conducted using de-identified patient information from Optum Electronic Healthcare Record (EHR) (2007–2019), Optum Clinformatics Data Mart (CDM) (2004–2019) and IBM MarketScan (2007–2019) databases. YF vaccine recipients were identified using relevant vaccination and procedural codes. Demographic characteristics and pre-existing medical conditions were described. Incidence proportions with 95% confidence intervals (CI) of neurotropic and viscerotropic diseases occurring ≤ 30 days post-vaccination, after exclusion of unlikely cases based on current clinical guidelines of YEL-AND and YEL-AVD, were calculated. Results: A total of 92, 205, 46, 539 and 125, 235 YF vaccine recipients were retrieved from Optum EHR, Optum CDM and IBM MarketScan databases, respectively. The majority of vaccine recipients were aged < 60 years (highest proportion aged 18–29 years) with a higher proportion of females overall. Few vaccine recipients (<1%) had conditions predisposing them to immunosuppression. Four non-fatal cases of neurotropic disease and zero cases of viscerotropic disease were identified. The incidence proportion of post-vaccination neurotropic disease was 1.41 (95% CI: 0.15–6.61) and 3.04 (95% CI: 0.86–8.11) per 100, 000 vaccine recipients in Optum EHR and IBM MarketScan, respectively, with no events identified in Optum CDM. Conclusions: This study provides updated insights into current YF vaccine usage in US civilian recipients and supports the safety profile of YF vaccines in US practice. The low frequency of pre-existing immunosuppressive medical conditions among vaccine recipients suggests good adherence to vaccination guidelines by healthcare practitioners. The risk of developing neurotropic and viscerotropic disease post-vaccination remains rare.